Migration, incorporation, and change in an interconnected world - Ali, Syed, 1968-; Hartmann, Douglas (New York : Routledge, 2015)
'Written in engaging and approachable prose, Migration, Incorporation, and Change in an Interconnected World covers the bulk of material a student needs to get a good sense of the empirical and theoretical trends in the field of migration studies, while being short enough that professors can easily build their courses around it without hesitating to assign additional readings. Taking a unique approach, Ali and Hartmann focus on what they consider the important topics and the potential route the field is going to take, and incorporate a conceptual lens that makes this much more than a simple relaying of facts.'--
Includes bibliographical references and index.
Keywords: Emigration and immigration -- Study and teaching; Assimilation (Sociology) -- Study and teaching; Social change -- Study and teaching